THE INFLUENCES OF BRAND PERSONALITY FROM CELEBRITY ENDORSER TO ATTITUDE TOWARDS ADVERTISING (Study On Super O2 Advertising Starring By Nadine Chandrawinata) - Bayaqy, Diyo Ahmad (Jurnal Ilmiah Mahasiswa FEB, 2016)
This research to analyze the influence of brand personality factors which consist of excitement, professionality, wellness, humanity, and status enhancement on attitude towards advertising (studies on SuperO2 advertising that starred by Nadine Chandrawinata). This research using explanatory research and the sample was 212 respondents. Sampling was carried out with non-probability sampling method using purposive sampling. Test equipment used to test the research instruments such as validity test, reliability test and test the classical assumption of normality test, multicolinearity test and heteroscedasticity test. For data analysis techniques using multiple linear regression analysis. Hypothesis testing using F test, and t test.The results showed that  the excitement, professionality, wellness, humanity, and status enhancement has an effect simultaneously on attitude towards advertising. The analysis also showed that partial relationship of each variable which all variable called excitement, professionality, wellness, humanity, and status enhancement significantly influence to attitude towards advertising. The result also showed that the varible wellness has the more influence than other variable.   Keywords: Brand Personality, Excitement, Professionality, Wellness, Humanity, Status Enhancement, Super O2, Advertising.